Outcome of plerixafor based stem cell (CD34) mobilisation in autologous stem cell transplant. A Retrospective analysis from a tertiary care centre of Pakistan - Farrukh Ali Khan; Fawad Qureshi; Urooj Haider Hashmi (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the outcome of plerixafor-based stem cell mobilisation in autologous stem cell transplant. Method: The retrospective study was conducted at the Dow University Hospital, Karachi, and comprised data from February 2019 to December 2024 related to patients who had undergone autologous bone marrow transplant. The outcome of stem cell mobilisation with plerixafor was based on the percentage of patients who achieved the target cell yield of >2×106 cells/kg after plerixafor administration. Adverse effects with plerixafor-based stem cell mobilisation were noted. Data was analysed using SPSS 26. Results: Of the 35 patients with median age 32 years (interquartile range: 27-46 years), 20(57.1%) were males and 15(42.9%) were females. Median stem cell count after only one dose of plerixafor was 2.9x106 cells/kg (IQR: 2.1-6.0) and 31(88.5%) patients achieved the cut-off value after only 1-2 doses of plerixafor. Median time of neutrophil engraftment after transplant was day 11 (interquartile range: 10-15.5 days), and for platelet engraftment it was day 13 (interquartile range: 11-21 days). Overall, 7(20 %) patients experienced body aches with maximum severity being grade II which was controlled with analgesics. Conclusion: Plerixafor-based stem cell mobilisation in autologous bone marrow transplantation was found to be effective, having minor side-effects. Key Words: Plerixafor, CD34 stem cell mobilisation, Autologous stem cell transplantation.